Lectinhistochemical staining of granuloma induced by bacillus Calmette-Guerin in Piaractus mesopotamicus - Wilson Gómez Manrique; Gustavo da Silva Claudiano; Mayra Araguaia Pereira Figueiredo; Thalita Regina Petrillo; Paulo Fernandes Marcusso; Eduardo Juan Gimeno; Julieta RE. Moraes; Flávio Ruas de Moraes (2013)
ABSTRACTObjetive. This study was conducted to evaluate, by means of lectinhistochemistry (LHC), the expression of carbohydrates in granulomas induced by the bacillus Calmette-Guerin (BCG) in muscle tissue of Piaractus mesopotamicus after 33 days. Material and methods. Histological sections with 3 μm thick were incubated with the following lectins :WGA (Wheat germ agglutinin), DBA (Dolichos biflorus agglutinin) and HPA (Helix pomatia agglutinin), and the results were evaluated by light microscopy. Results. Acid fast bacilli were stained by Ziehl Neelsen (ZN) and strong labeled by WGA in the cytoplasm of macrophages. Labeling with DBA was intense in fibroblasts and weak in macrophages. On the other hand, HPA binding was stronger in macrophages, especially in those that were in close contact with epithelioid cells, without evidence of binding to fibroblasts. The epithelioid cells were not labeled by the used lectins, but they were identified by Hematoxilin-Eosin (HE). The lectins labeled specific type saccharides in glycoproteins, as N-acetylglucosamine present in bacilli and macrophages, as well as N-acetyl-galactosamine in macrophages. The control group showed no inflammation or lectin binding. Conclusions. This technique may be useful in identifying receptors for WGA, DBA and the HPA lectins in epithelioid granuloma induced by BCG in P. mesopotamicus